Optimal utilization of available resources including land and office space by the government of Haryana following reforms: a case study - Kothari, Sanjay; Walia, Kiran Lekha (2005)
This case study presents relevant facts as to how district authorities in Haryana in past optimized land usage in wake of successive reforms by the government following creation of Haryana in late sixties. The case study is based on efforts for enhanced land usage and thus includes steps taken to optimize space utilization within government buildings in accordance with the prescribed norms. With ever growing increase in population, it is suggested that unless timely suggested course corrections are applied and norms for space allocation strictly adhered to in letter and spirit, it may not be possible to achieve the goal of optimum resource utilization such as land and office space which are very scarce and expensive anywhere in the country. - Reproduced.
Keywords: District administration - India - Haryana; District administration